Synthesis and properties of the conjugated polymers with indenoindene and benzimidazole units for organic photovoltaics. Issue 2 (12th October 2012) - Shim, Joo Young; Lee, Byoung Hoon; Song, Suhee; Kim, Heejoo; Kim, Ju Ae; Kim, Il; Lee, Kwanghee; Suh, Hongsuk
Abstract A new electron deficient unit, dimethyl‐2H‐benzimidazole (MBI), and dihydroindeno[2, 1‐a]indene (ININE) moiety as electron‐rich unit were coupled to synthesize the conjugated polymers containing electron donor–acceptor pair for organic photovoltaics. ININE, MBI, and thiophene (or bithiophene) units were incorporated using Stille and Suzuki polymerization to generate poly(2, 7‐(5, 5, 10, 10‐tetrakis(2‐ethylhexyl)‐5, 10‐dihydro‐ indeno[2, 1‐a]indene)‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2, 2‐dimethyl‐2H‐benzimidazole)) (PININEDTMBIs) (or PININEBBTMBIs). In MBI, the sulfur at 2‐position of 2, 1, 3‐benzothiadiazole (BT) unit was replaced with dialkyl‐substituted carbon, whereas keeping the 1, 2‐quinoid form, to improve the solubility of the polymers. The field‐effect hole mobility of PININEBBTMBI was 3.2 × 10−4 cm2/Vs which was improved as compared to that of PININEDTMBI (2.7 × 10−5 cm2/Vs) caused by the introduction of bithiophene units. In case of the most efficient polymer, PININEBBTMBI, the device with the configuration of indium tin oxide (ITO)/poly(3, 4‐ethylenedioxythiophene) (PEDOT):polystyrene sulfonate (PSS)/polymer:PC71BM(1:4 w/w)/Al, annealed at 100 °C for 10 min demonstrated a open circuit voltage of 0.78 V, a short‐circuit current density of 6.66 mA/cm2, and a fill factor of 0.41, leading to the power conversion efficiency of 2.11%, under white‐light illumination (AM 1.5 G, 100 mW/cm2). © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013